Challenges Experienced By Postgraduate Candidates in the Application of Conceptual Frameworks in Scientific Research (International Journal of Scientific Research and Management (IJSRM), 2022)
Conceptual framework brings all aspects of a study together through a process that explicates their connections and the contexts shaping a research setting as well as the study of the phenomena in that setting. It gives a theoretical meaning to what is contained in the main text of the study. The aim of this study was to understand challenges faced by postgraduate students in the application of conceptual frameworks in their researches. The study was informed by a case study and interpretivist paradigm. Participants were made up of four lecturers and twenty postgraduate students. The study findings suggest that students did not understand what the conceptual framework was really about such that, even those who had some ideas could not precisely apply it. This situation was partly attributed to poor understanding by supervising lecturers and lack of prioritization in teaching conceptual frameworks during learning process as well as lack of interactive supportive materials. The study further revealed that students did not substantively review literature to understand their research area that would eventually help them develop shrewd conceptual framework. It was also found that many students who purported to use conceptual framework failed to explain and relate it to methods and findings. Premised on the study findings, the study says that, postgraduate candidates lacked explicit and cohesive understanding of the relationships among concepts throughout the research process, they instead focused on the methods whilst overlooking the conceptual framework. The problem with application of conceptual framework was not only on trainees, but also on the trainers both of whose defensive arguments tended to be projected towards the opposite party. This therefore calls for a critical individual reflection and reflexivity on both parties and to ensure a co-engaged way of teaching and learning that is transformatively hands-on from the onset. The study proposes a framework that can generally enhance effective teaching of complex topics in research methodology courses at all academic levels.